2023
DOI: 10.3390/app13085038
|View full text |Cite
|
Sign up to set email alerts
|

Novel Highly Dispersed Additive for Proton-Conducting Composites

Abstract: The proton conductivity and structural properties of (1–x)CsH2PO4–xZnSnO3 composites with compositions of x = 0.2–0.8 were studied. Zinc stannate ZnSnO3 was prepared by the thermal decomposition of zinc hydroxostannate ZnSn(OH)6, which was synthesized by hydrolytic codeposition. To optimize the microstructure of ZnSnO3, thermal decomposition products of ZnSn(OH)6 were characterized by thermal analysis and X-ray diffraction, Fourier transform infrared spectroscopy, low-temperature nitrogen adsorption, and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…), which can be obtained via thermolysis of precursors, -hydroxostannates of the MSn(OH) 6 type. It should be noted that stannates obtained via thermolysis are characterized by a relatively high specific surface area (within 10...100 m 2 /g) and can be used as functional additives for obtaining composite materials [49].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), which can be obtained via thermolysis of precursors, -hydroxostannates of the MSn(OH) 6 type. It should be noted that stannates obtained via thermolysis are characterized by a relatively high specific surface area (within 10...100 m 2 /g) and can be used as functional additives for obtaining composite materials [49].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have shown that the addition of MSn(OH) 6 thermolysis products, -nanocomposites based on MSnO 3 (M = Mg, Ca, and Sr) with a small admixture of SnO 2 , leads to an increase in the ionic conductivity of cesium nitrite by more than an order of magnitude [53,59]. Recently, it was found that the addition of zinc stannate to cesium dihydrophosphate leads to an increase in the proton conductivity of the salt in the lowtemperature region and an improvement in the stability of the proton electrolyte in the high-temperature region [49]. It is also known that the introduction of oxides with proton conductivity into acidic salts leads to an increase in their proton conductivity [48,60].…”
Section: Introductionmentioning
confidence: 99%